1997
DOI: 10.1042/cs0920511
|View full text |Cite
|
Sign up to set email alerts
|

HPLC Glycosaminoglycan Analysis in Patients with Graves' Disease

Abstract: 1. Orbital accumulation of hydrophilic, interstitial glycosaminoglycans (GAGs) and subsequent expansion of retrobulbar tissue lead to the clinical manifestation of exophthalmos in patients with Graves' eye disease. 2. A highly specific method to determine the concentration and biochemical composition of different GAGs was developed in order to obtain a sensitive test system for the activity of the disease. By means of this method, GAG excretion in 24 h urine collections of 56 patients and 21 controls was analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 16 publications
2
19
0
1
Order By: Relevance
“…Serum from healthy blood donors instead of serum from patients was chosen for our study to avoid changes in serum GAGs by pathological mechanisms in patients. Consistent with the literature [16] no association between gender and GAG amount was detected. The XYLT1 SNP c.343GNT in the heterozygote state was associated with a significantly decreased GAG amount compared to serum from blood donors who were non-carriers of all SNPs investigated.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Serum from healthy blood donors instead of serum from patients was chosen for our study to avoid changes in serum GAGs by pathological mechanisms in patients. Consistent with the literature [16] no association between gender and GAG amount was detected. The XYLT1 SNP c.343GNT in the heterozygote state was associated with a significantly decreased GAG amount compared to serum from blood donors who were non-carriers of all SNPs investigated.…”
Section: Discussionsupporting
confidence: 93%
“…NM_022167 for XYLT2). [6,7,15,16]. Genetic polymorphisms in the genes relevant for glycosaminoglycan biosynthesis could be a risk factor for development and the severity of diseases that are associated with changes in the GAG metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, present investigations focus on sites with obvious clinical disease (orbit and lower extremity) with the intuitive assumption that such localization of disease must involve cellular and/or biochemical differences between different regions of the body. However, previous studies have raised the possibility that Graves' disease may have a systemic, connective tissue systemic component (27)(28)(29)(30)(31)(32)(33). Perhaps the strongest evidence for this notion is increased urinary excretion of mucopolysaccharides or glycosaminoglycans in Graves' patients with, as opposed to without, GO (28,32).…”
Section: Discussionmentioning
confidence: 93%
“…Perhaps the strongest evidence for this notion is increased urinary excretion of mucopolysaccharides or glycosaminoglycans in Graves' patients with, as opposed to without, GO (28,32). Moreover, Hansen et al found increased urinary GAG excretion in Graves' disease independent of the presence of ophthalmopathy (33). It is difficult to explain increased urinary excretion of GAG with involvement of only a few grams of orbital tissue.…”
Section: Discussionmentioning
confidence: 97%
“…The extra-ocular muscles (EOM) can be enlarged in TED, primarily due to oedema, but the myocytes themselves are relatively unaffected (Hufnagel et al 1987). Two further processes increase the contents of the orbit, production of glycosaminoglycans by orbital fibroblasts (Hansen et al 1997) and hypertrophy and hyperplasia of the adipose tissue (Sorisky et al 1996). The increase in fat cell number is the consequence of adipogenesis, in which preadipocytes differentiate into mature adipocytes.…”
Section: Introductionmentioning
confidence: 99%